PERENCANAAN KONSTRUKSI STRUKTUR ATAS SERTA STRUKTUR HELIPAD PADA BANGUNAN RUMAH SAKIT R K CHARITAS PALEMBANG - WINNESS SUTEHNO (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
In this thesis, it is discussing the design construction of super structure and helipad structure of the building of R K Charitas hospital situated in Jenderal Sudirman street Palembang. The building which has function as hospital clinic consisting of 8 stories with 39 meters height of building is analyzed with lateral resistant Special Moment Resisting Frame System, according to seismic design category of this building which belongs to C category. The calculation refers to valid standards, namely : SK SNI 03-2847-2002 tentang Tata Cara Perhitungan Struktur Beton untuk Bangunan Gedung dan SNI 1726-2012 tentang Tata Cara Perencanaan Ketahanan Gempa untuk Struktur Bangunan Gedung dan Non Gedung. And another standard which is applied in is Pedoman Perencanaan Pembebanan Untuk Rumah dan Gedung (PPPURG) 1987. With helicopter load on this top building, the analysis is based on spectrum response dynamic with software called as SAP2000 V14. The analysis contains of the reinforcement steels of column, balk, slab, and also helipad which is on this top building and the control in joint displacement deviation of this building which dues to service limit and ultimate limit. From the result of analysis of this thesis, it is resulting dimensions and number and size of the reinforcement steels of super structure which contain of column, balk, slab, and also helipad structure and maximum joint displacement deviation impacted by all loads running on the building of R K Charitas Hospital Palembang. Key Words : Super Structure, Helipad, Charitas, SMRFS, SNI 1726-2012, Joint Displacement Deviation.